Challenges of service procurement: a case study at the second rural transport improvement project of Local Government Engineering Department - Shiddique, Md. Rayhan (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.